2021
DOI: 10.1002/cpp.2664
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive negative thinking, metacognitive beliefs, and their interaction as possible predictors for problematic cannabis use

Abstract: The metacognitive formulation of addictive behaviours considers repetitive negative thinking (RNT) and metacognitive beliefs as two important processes involved in the development and maintenance of addictive behaviours. To date, very limited research has investigated the implication of these processes in problematic cannabis use. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…What this does imply, is that the effects of cannabis may lead users to be more subjectively aware of changes in cognitive patterns. Previous research somewhat supports this notion, as: a) alcohol use has been reported to decrease awareness (Love, Rowland, et al, 2022), due to deficits in judgement and perception (Dasgupta, 2017); and b) cannabis, has been reported to increase awareness (Love, Rowland, et al, 2022) and has been associated with an inclination for cognitive self‐consciousness (Hamonniere et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…What this does imply, is that the effects of cannabis may lead users to be more subjectively aware of changes in cognitive patterns. Previous research somewhat supports this notion, as: a) alcohol use has been reported to decrease awareness (Love, Rowland, et al, 2022), due to deficits in judgement and perception (Dasgupta, 2017); and b) cannabis, has been reported to increase awareness (Love, Rowland, et al, 2022) and has been associated with an inclination for cognitive self‐consciousness (Hamonniere et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“… 93 Delayed memory was not associated with CUD onset among teens in one longitudinal study, 94 and findings of a cross-sectional study suggest dimensions of repetitive negative thinking is not associated with cannabis use problem severity although dimensions of metacognitive thinking are. 95 In a longitudinal study, cannabis-harm implicit association test scores significantly predicted concurrent risk of CUD and use such that stronger cannabis-harm associations were associated with less use and risk of CUD. 96 Finally, harmonious passion was a stronger predictor of increased consumption than was obsessive passion, whereas obsessive passion was a stronger predictor of CRNCs longitudinally.…”
Section: Resultsmentioning
confidence: 98%
“…Evidence also supports that ruminative thinking cross‐sectionally and prospectively predicts drinking status and substance use severity and that RNT mediates the relationship between emotional symptoms (e.g., anxiety and depression) and SUD symptoms (Adrian et al, 2014; Devynck et al, 2019; Grynberg et al, 2016; Hamonniere et al, 2020, 2021; Heggeness, 2021; Wolitzky‐Taylor, 2021). In addition, RNT has been found to increase negative emotions or cravings and to lead to substance use (Nolen‐Hoeksema & Harrell, 2002).…”
Section: Supporting Evidence For the Process‐based Analysismentioning
confidence: 90%